AI-Driven Media Evolution: Exploring Automated Journalism’s Impact on Industry’s Future - Hafied, Hasdiyanto; Irwanto, Irwanto; Surjatmodjo, Dwi; Latuheru, Rido (Jurnal Kajian Jurnalisme, 2025)
Today, mass media experiences significant developments with respect to the introduction of automated journalism systems in the age of artificial intelligence (AI). This study looks into how Indonesian media organizations respond to and deploy automated journalism technologies. Specifically, it focuses on how newsroom practices and professional roles change. The study investigated three key aspects of automated journalism-technology integration, ethics, and workforce adaptation based on a systematic literature review and secondary interview data obtained from industry practitioners. It explored the problems encountered in the implementation of automated journalism. This study found that automated journalism has been successfully integrated into news production to improve efficiency and quality. However, its integration within existing organizational facets is challenging, demanding heavy cultural updates, and professional skills development. Also, effective integration of AI into newsrooms depends on ethical frameworks and quality control infrastructures to ensure that the benefits of automated content generation do not come at the expense of journalistic quality. Furthermore, unlike many fears of job loss associated with its usage, automated journalism can also create new hybrid positions where journalists have leveraged technical knowledge to complement fact-checks and storytelling.